Diabetes Burden in Urban and Rural Senegalese Populations: A Cross-Sectional Study in 2012 - S. M. Seck; D. G. Dia; D. Doupa; A. Diop-Dia; I. Thiam; M. Ndong; L. Gueye (International Journal of Endocrinology)
Diabetes represents a challenging global health issue in the 21st century. Data from sub-Saharan African populations are scarce and are usually restricted to urban settings. The objective of this study was to compare prevalence and risk factors of diabetes in rural and urban areas in Senegal. Methods. In a community-based survey between January and May 2012, we included 1027 adults aged ≥18 years living in northern Senegal. Sociodemographic, clinical, and biological data were collected during household visits. Multivariate logistic regression was performed to identify factors associated with diabetes. Results. Mean age of participants was 48.0±16.9 years and 65.7% were female. Participants from urban area represented 55.7%. The age-standardized prevalence of diabetes was 7.6% (6.0% in men versus 9.0% in women). Prevalence of diabetes was higher in urban areas (8.1%) compared to rural areas (4.6%). Disease awareness rate was 43%. After multivariate analysis, age (OR = 1.63, p=0.001), familial history of diabetes (OR = 1.42, p=0.001), and abdominal obesity (OR = 1.17, p=0.05) were associated with diabetes. Conclusion. Diabetes is frequent in urban and rural areas in Senegal. Awareness rate is very low among populations. Age, family history of diabetes, and abdominal obesity are the main risk factors identified.